Is Neck Circumference a Marker for Cardiovascular Risk in Obese Adolescents? - Faria, Bruno; Escrivão, Maria Arlete Meil Schimith; Nogueira, Paulo Cesar Koch (International Journal of Child Health and Nutrition, 2016)
Background: Weight excess has become a public health problem worldwide, reaching about 200 million children, of whom 40 to 50 million are obese. Obesity in childhood is associated with increased blood pressure (BP), high triglycerides, low HDL-cholesterol and abnormal glucose metabolism. Visceral fat is a stronger predictor of metabolic dysfunction and cardiovascular risk than total body adiposity. Assessment of neck circumference (NC) is an easy method, which can serve as screening to identify individuals with weight excess. Our study aim was to examine associations between NC with BP values, lipid profile, blood glucose and fasting insulin in obese adolescents and verify the reproducibility of measurements of NC. Methods: 82 adolescents aged 10 to 17 years were included in the study, being 43 (22 boys and 21 girls) with obesity and 39 with normal weight (20 boys and 19 girls). Results: Significant associations were observed between NC and BMI, BP, HDL cholesterol, insulin and HOMA-IR. Disagreement between both observers for NC was observed in 5.2% of the sample, only concerning obese individuals. Conclusion: Our findings strengthen the knowledge about the potential value of NC as a tool for identifying patients at risk for hypertension, insulin resistance, and obesity. However as with the waist circumference it may be flawed in obese individuals.